(untitled) (Acta Scientiarum. Health Sciences, 2015)
Differences between reactive oxygen species and antioxidant defense system unbalance the redox status. The exposure to cigarette smoke can increase this imbalance. Trans-resveratrol is a polyphenol with great antioxidant action that reduces the oxidative stress. This study investigated the effect of the trans-resveratrol supplementation on the cardiac oxidative stress in rats exposed to cigarette smoke. Male Wistar rats were randomized into four groups: Control Group (CG), Exposure to Smoke Group (ESG), Antioxidant Group (AG) and Exposure to Smoke plus Antioxidant Group (ESAG). Animals were exposed to cigarette smoke and supplemented with trans-resveratrol (6.0 mg kg-1) for two months. The lipid peroxidation (TBARS) and the enzymatic activity of catalase (CAT) were measured in the cardiac muscle. The ESG presented the highest lipid peroxidation level compared with CG (p < 0.001), AG (p < 0.001) and ESAG (p < 0.006). The CAT activity was higher in the AG (p < 0.001) and ESAG (p < 0.001) compared with CG. The ESG presented lower CAT activity compared with the ESAG (p < 0.001). The supplementation of Trans-resveratrol attenuated the cardiac oxidative stress and increased the activity of catalase. Our findings evidenced the cardioprotective effect of trans-resveratrol in rats exposed to cigarette smoke.